2013
DOI: 10.3366/ijhac.2013.0084
|View full text |Cite
|
Sign up to set email alerts
|

An Approach to Analyzing Working Practices of Research Communities in the Humanities

Abstract: The need for a firm understanding of the working practices of researchers in the humanities emerges as a prerequisite for the development of effective digital research infrastructures. This paper will focus on the rationale behind the design and implementation of two related studies conducted in the context of two European e-Infrastructures projects, DARIAH and EHRI. Within DARIAH the challenge involved conducting, analysing and understanding research practices of arts and humanities researchers, a largely ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 4 publications
0
19
0
1
Order By: Relevance
“…But collaboration remains challenging in digital humanities and digital curation alike (Abbott, ; Alexogiannopoulos et al, ; Benardou et al, ; Maron & Pickle, ; McCarty, ; Molloy, ; Waters, ). It depends on achieving common understandings of language and terminology, methods and research styles, and theories, outputs, and values (Siemens et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…But collaboration remains challenging in digital humanities and digital curation alike (Abbott, ; Alexogiannopoulos et al, ; Benardou et al, ; Maron & Pickle, ; McCarty, ; Molloy, ; Waters, ). It depends on achieving common understandings of language and terminology, methods and research styles, and theories, outputs, and values (Siemens et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier qualitative and mixed methods research by my DCU colleagues and myself on scholarly practices and digital needs of humanities researchers, including archaeologists, confirmed the validity of a categorization of research processes such as digital and non-digital information seeking, resource organization, processing, collaboration, and dissemination [154]. In tandem with information seeking, we found that archaeologists also engage in the active curation of a continuous range between data and scholarly objects, transforming "raw" into "institutional" facts [42] through description, classification, interpretation and publication.…”
Section: Accounting For Archaeological Curation Practice and Methodsmentioning
confidence: 99%
“…This model can reach beyond the custodial fold of secondary archaeological archives and repositories to encompass digital curation from "the trowel's edge" to dynamic online publication, review, and annotation. On the other hand, the complementary in scope Scholarly Research Activity Model [143], developed by the DCU on the basis of an evidence-based study of scholarly research processes in archaeology, history and other humanistic disciplines [153,154], may serve as a useful foundation for capturing salient dimensions of archaeological curation in practice. These include the differentiation between normative and actualistic aspects of archaeological research practice (i.e., between a method or established procedure and its application), the interaction of multiple actors (including archaeologists, local and source communities, and audiences) and their motives and goals, the sociotechnical adoption of methods, procedures, tools and services by archaeological communities of practice, the primacy of indexed "things in the world" for archaeological interpretation, and the multiple actions of curating archaeological information entities (e.g., refers to, creates, updates, annotates, classifies, aggregates, samples, modifies, etc.)…”
Section: Developing An Operational Theory Of Archaeological Digital Cmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of interviews in the context of the European Digital Research Infrastructure in the Arts and Humanities (DARIAH) indicates how scholars routinely engage in the active curation of data and scholarly objects, transforming ''raw'' into ''institutional'' facts (Searle 2006) through annotation and edition, scholarly writing and publication (Benardou et al 2010b). In a follow-up study in the context of the European Holocaust Research Infrastructure (EHRI), researchers were found to engage in diverse curation microactivities such as annotating, organizing, and versioning (Benardou et al 2013), through which they were seen to modify, create, or destroy instances of all kinds of information objects related to their inquiry: conceptual representations not just of objects encountered, but also, in tandem, of activities, actors, concepts, and other related entities. As in the case of museum collections work (Trant 2007), a process of knowledge curation is manifested here, situated not just in objects mediated through their digital surrogates, but also in a network of heterogeneous information-laden entities from the world of events, properties, and kinds which they index.…”
Section: A Pragmatic Approach To Digital Curationmentioning
confidence: 99%